The Relationship Between The Perception of Professional Identity and The Professionalism Level of Medical Students - Luthfianasari, Luthfianasari; Pamungkasari, Eti Poncorini; Hermasari, Bulan Kakanita (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: Medical education aims to create professional doctors through standardized methods according to the needs of public health services. A doctor must have a professional attitude and ability as a form of professional responsibility. Professionalism is often associated with professional identity, where professionalism is deemed necessary to be supported by professional identity. This study aims to determine the relationship between perceptions of professional identity and medical students’ professionalism level.Methods: A cross-sectional study was conducted in a faculty of medicine in Indonesia.  The respondents were medical students from 3 cohorts: 2019, 2020, and 2021. The data analysis used the Spearman correlation test.Results: A total of 276 respondents consist of 94 (34.1%) male and 182 (65.9%) female respondents. The mean scores for the professionalism level for batches 2019, 2020, and 2021, respectively, were 160.23, 160.83, and 162.07. The mean scores for the perception of professional identity for batches 2019, 2020, and 2021, respectively, were 86.89, 89.26, and 89.18. The Spearman correlation test results showed there was a relationship between the professionalism level and perceptions of professional identity (p <0.001; r = 0,508), but there was no relationship between the professionalism level and study period (p = 0.081; r = -0.105).Conclusion: There is a relationship between perceptions of professional identity and the professionalism level of medical students.